ENERGY AND ELECTRONIC CHARGE CONSERVATION DURING ALPHA AND BETA EMISSION - Patra, Prasanta Kumar (SCHOOL SCIENCE, 2010)
In 1986, Antoine Henri Becquerel, a French physicist, while working on phosphorescen materials such as uranium salts, found that they emit radiations spontaneously. It was later established that a magnetic or an electric field splits such radiations into three beams. These radiations have been named after the first threeletters of the Greek alphabet, i.e., alpha (a), beta (b) and gamma (g). The first two radiations are corpuscles in nature so they are called particles whereas the third, being electromagnetic radiation, is called a ray. The elements, which spontaneously emit such type of radiations, are called radioactive elements and the phenomenon is known as radioactivity. For discovery of these radiations, Becquerel received Nobel Prize for Physics jointly with Marie Curie and Pierre Curie in 1903.